METHODOLOGICAL FOUNDATIONS OF THE ANALYSIS OF PATIENTS’ VIEWS ON THE PROCESS OF LASTING OF THEIR DISEASES IN THE FRAMEWORK OF MEDICAL ANTHROPOLOGY - Abduraxmonova K. R. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the methodological foundations of the analysis of patients’ views to disease detection, determination of diagnosis and treatment process within the framework of medical anthropology. The concept of the “Explanatory model”, developed by Arthur Kleinman, is used as the main methodology, and this model allows us to systematically determine the patient’s subjective experience in the way of understanding the disease, studying symptoms, and formulating treatment. The article also explores the religious, cultural, and social views of patients on surgery treatment, emphasizing the importance of cultural competence in healthcare practice.